( 1 + 1 ! x + 2 ! x 2 + 3 ! x 3 + … + n ! x n ) 2
For n ≥ 6 , if the coefficient of x 6 in the expansion above can be expressed as b a for coprime natural numbers a , b , find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Well, that was unexpected. I was thinking of the conventional 6 = 1 + 5 = 5 + 1 = 2 + 4 = 4 + 2 = 3 + 3 approach. Nicely done.
In response to Challenge Master: Thanks! Expansion seemed tedious, so I used this short method.
Actually how do you know before hand that the k t h term of the expansion will remain the same for all n > k without any proof? You have to prove for the general case and if you do that, then the coefficient of the k t h term will be of the form k ! 2 k and we can just substitute k = 6 and simplify to get answer. Or am I wrong here?
The n th term in the expansion of the square is A n x n = k = 0 ∑ n k ! x k ⋅ ( n − k ) ! x n − k = k = 0 ∑ n k ! ( n − k ) ! x n . Divide out x n and multiply by n ! : n ! A n = k = 0 ∑ n k ! ( n − k ) ! n ! = k = 0 ∑ n ( n k ) . In other words, we must sum over an entire row in Pascal's triangle. It is well known that the sum equal a power of two: n ! A n = 2 n , from which it follows that A n = n ! 2 n . In the case of n = 6 , A 6 = 6 ! 2 6 = ( 1 ⋅ 3 ⋅ 5 ) ⋅ ( 2 3 ⋅ 3 ! ) 2 6 = 3 ⋅ 5 ⋅ 2 ⋅ 3 2 3 = 3 2 ⋅ 5 2 2 . It follows that a = 4 , b = 4 5 , and a + b = 7 .
We know that the x 6 term in the expansion will be the sum of the products of all terms in the parentheses with orders that add up to 6. We can view the problem as taking the sum of the products of the coefficients of these terms. To account for the fact that we are squaring the sequence, we must multiply every term in our sum by 2 (except for the term obtained by multiplying the coefficients of terms with equal orders). The problem is now in the form 2 ( 6 ! 1 + 1 ! 5 ! 1 + 2 ! 4 ! ) 1 + 3 ! 3 ! 1 ) . This expression can be simplified to the fraction 4 5 4 . 4 + 4 5 = 4 9 = 7
Just take the limit as n → ∞ of the whole expression and you get e 2 x and the coefficient of x 6 of the Taylor expansion of e 2 x is 4 / 4 5 and taking square root of 49 gives you 7 and that's the answer
O n l y t e r m s t h a t g i v e x 6 a r e g i v e n b e l o w . 1 ∗ 6 ! x 6 + 1 ! x ∗ 5 ! x 5 + 2 ! x 2 ∗ 4 ! x 4 + 3 ! x 3 ∗ 3 ! x 3 + 4 ! x 4 ∗ 2 ! x 2 + 5 ! x 5 ∗ 1 ! x + 6 ! x 6 ∗ 1 = 2 ∗ { 1 ∗ 6 ! x 6 + 1 ! x ∗ 5 ! x 5 + 2 ! x 2 ∗ 4 ! x 4 } + 3 ! x 3 ∗ 3 ! x 3 = x 6 { 6 ! 2 + 5 ! 2 + 2 ! ∗ 4 ! 2 + 3 ! ∗ 3 ! 1 } = x 6 { 3 6 0 1 + 6 0 1 + 2 4 1 + 3 6 1 } = 3 6 0 x 6 ∗ { 1 + 6 + 1 5 + 1 0 } = x 6 4 5 4 = x 6 b a . ∴ 4 + 4 5 = 7
Write the above expansion as ζ =
( e x − ∑ i + 1 ∞ x n + i / ( n + i ) ! ) 2
= e 2 x − ( t e r m s − n o t − c o n t a i n i n g : x 6 )
⟹ c o e f f x 6 i n : ζ = 6 4 / 6 ! = 4 / 4 5
Therefore answer is 4 + 4 5 = 4 9 = 7
Problem Loading...
Note Loading...
Set Loading...
The coefficient of x 6 will be the same for all n ≥ 6 , so we can assume n → ∞ . The expression becomes ( e x ) 2 = e 2 x .
The coefficient of x 6 in the Taylor expansion of e 2 x will be 6 ! 2 6 = 7 2 0 6 4 = 4 5 4 .
4 + 4 5 = 7 □